Acute and Subchronic Toxicity of Indonesian House Dust Mites (IHDM) Allergenic Extract for Asthma Allergy Immunotherapy - Aniek Setiya Budiatin; Yusuf Alif Pratama; Winda Fatma Sari; Mahardian Rahmadi; Muhammad Taher; Zainul Amiruddin Zakaria; Junaidi Khotib (Universitas Airlangga, 2022)
Background: In developing a pharmaceutical product, it is necessary to conduct pre-clinical and clinical trials to ensure its safety and effectiveness. The toxicity test is conducted to assess the safety of a substance to determine its toxic effect of the substance. Objective: This study aims to determine the acute and subchronic toxicity of administering IHDM allergenic extract using experimental animal models. Methods: Female BALB/c mice and female and male Wistar rats were used as experimental animal models. While the IHDM allergenic extract was used with the level of Der p1 is 11.3-26.6 ng/mL and was administered by intravenous route. The acute toxicity test was carried out for 14 days on four different dose groups of experimental animals. The subchronic toxicity test was carried out for 28 days using three other dose groups of experimental animals. Results: The administration of a single dose of IHDM allergenic extract at various doses did not cause mice behaviour changes, and no death was shown in each group. Likewise, there was no change in the principal organs by macroscopic observations. Meanwhile, administering IHDM allergenic extract at repeated doses for 28 days could show signs of toxicity. The symptoms were shown in the histopathological structure of the liver, kidney, and heart organs. Conclusion: It can be concluded that the IHDM allergenic extract is safe for single-dose administration but shows toxic signs when given in repeated doses. Further tests are needed for 90 days of subchronic toxicity and satellite testing.